21-Year-old Woman with a Headache (Out of Print) - Grace Huang (Association of American Medical Colleges, 2006)
Abstract This is a web-based virtual patient case about a 21-year-old White (non-Hispanic) female diagnosed with migraines and central nervous system tumor.